STUDI LAMA PERENDAMAN DAN JENIS MEDIA TANAM TERHADAP PERTUMBUHAN STEK PUCUK JATI (Tectona Grandis L.) - Martha Benu; Shirly S Oematan; Wilhelmina Seran (Wana Lestari, 2021)
Plant propagation is easy to do and does not require a lot of money it is propagation through seeds (generative). Efforts that can be made to reproduce teak plants by vegetative propagation used the seeding of tree shoots or by shoot – cuttings. In the propagation of shoot – cuttings that need to be considered is the use of the type of media planting and the use of growth hormones to accelerate root growth. This study was conducted to determine the interaction between the application of media planting and the duration of immersion the substance of Rootone-F on the growth of teak (Tectona grandis L.) shoot – cuttings. The experimental design carried out was a 2 (two) – factorial factor experiment that arranged completely randomly. The first factor was the length of immersion in the growth substance of Rootone-F, which consisted of 3 (three) levels, namely, direct immersion, 5 minutes of immersion, and 10 minutes of immersion; the second factor is the influence of planting media which consists of several doses on 5 (five) media planting, which includes, 1 – 2.5 kg of soil, 2.5 kg of sand, 1 – 2 kg of husk charcoal, 1 – 2 kg of sand, and 1 – 2 kg of compost. The results showed that the interaction of the application of Rootone-F and the media planting showed a significant effect on the age of the shoots – out and the length of the shoots. The factor of giving Rootone-F and media planting had a very significant effect on the parameter of observing the number of leaves.